A new genus and two new species of Antillocorini (Hemiptera: Heteroptera: Rhyparochromidae: Rhyparochrominae) from Mexico and Guatemala - Brailovsky, Harry (Zootaxa, 2010)
One new genus Branstettocoris and two new species Branstettocoris pinguis (Mexico) and Branstettocoris parvulus (Guatemala) are described, illustrated, and included in the tribe Antillocorini (Rhyparochromidae). A key to the known genera of Mexican and Guatemalan Antillocorini is presented.